Social Commerce Trust Factors and Users' Perspectives: A Study in UAE Based on Trust-Extended Technology Acceptance Model - Abdulrazzaq, Reem (2019)
Nowadays, social commerce has been turned into the most interactive and the most convenient way in online shopping. Despite having multiple risks when performing a purchase through social networks, yet it is becoming the trend of the era. For that, the significance of trust has arisen along with the need to recognize the elements that influence trust in social commerce. These basic elements were identified as familiarity, electronic word-of-mouth, high knowledge in internet and social networks and integration between ecommerce and social commerce. The aim of this research study is to investigate the factors affecting UAE people’s trust in social commerce and have a closer look on users’ points of view when making a purchase process over social networks marketplaces. In order to accomplish this goal, a quantitative survey was carried out and the results were analyzed which provided us with an extensive vision about the perspectives of the respondents and the socio-technical components that affect users trust in social commerce.